Evolution of the biodiversity of trilobites from the Devonian of North Africa: taxonomic richness, morphological disparity and environmental impact - (:unkn) unknown (My University, 2021)
The effect of environmental changes on current biodiversity is a major concern. Understanding the impact of these changes on past biodiversity is one of the keys to interpret current and future upheavals. The trilobites have undergone many changes favourable to their diversification as well as many crises leading them close to extinction. Their fossils abound in North Africa, which make it an ideal region to study them. The objective of this thesis was to estimate the variations in the biodiversity of trilobites in this region and to identify their origins and consequences from databases compiling all the occurrences of the literature. The first aspect of biodiversity studied was the taxonomic richness. Using different diversity indices, we assessed the major global trends and then regional variations. While generic diversity was low at the beginning of the Devonian, a subsequent marine regression led to an important diversification, observable at a global : the Pragian diversification. Trilobites reached a peak of diversity in the Emsian, but subsequently a succession of abrupt sea level changes associated with anoxia events severely affected them. Between the Eifelian and the Givetian, trilobites have lost more than 90% of their generic diversity. Generic diversity still decreased in the Frasnien and two orders disappeared. After the Kellwasser mass extinction at the Frasnian-Famennian boundary, a slight recovery occurred involving only the Proetida and Phacopida orders. The second aspect was to study the morphological disparity by using landmarks. This study of morphological variability showed the same trends as that of diversity with a significant number of innovations in the Lower Devonian. Among the novelties, there was the development of spiness. While the first biotic events only led to a slight loss of morphology, most forms disappeared in the Givetian. The most affected shapes are those that appeared in the Pragian and Emsian, while the forms
Keywords: African Research